Pemanfaatan Limbah Organik Terfermentasi Bokashi pada Budidaya Lele Dumbo (Clarias gariepinus): Dampak terhadap Performa Pertumbuhan dan Kelangsungan Hidup - Tania Octama Saputri; Arief Rachman B; Syaiful Ramadhan Harahap; Khairul Ihwan; Nurhasan Nurhasan (SIMBIOSA, 2026)
Feed costs and organic waste accumulation remain major constraints to efficient and sustainable catfish farming, creating the need to evaluate fermented quail manure bokashi as an alternative feed ingredient. This study assessed the most effective bokashi formulation for absolute length gain, absolute weight gain, and survival of juvenile Clarias gariepinus. Fish were reared for 60 days in a completely randomized design comprising four treatments with three replicates: 100% commercial pellets (P0), 100% bokashi (P1), 25% bokashi and 75% rice bran (P2), and 75% bokashi and 25% rice bran (P3). Among the bokashi-based diets, P3 produced the best performance, with an absolute length gain of 10.60 cm, an absolute weight gain of 55.33 g, and a survival rate of 95.00%. Dietary treatments did not significantly affect length or weight gain (p > 0.05) but significantly influenced survival (p < 0.001). The mean temperature, pH, and dissolved oxygen were 29°C, 7.19, and 5.46 mg L⁻¹, respectively, indicating suitable rearing conditions. Therefore, the P3 formulation offers potential as an organic-waste-based feed alternative, although it cannot yet fully replace commercial pellets and requires further evaluation of feed efficiency, nutrient retention, and waste balance.